2017
DOI: 10.1038/srep45460
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution RNA allelotyping along the inactive X chromosome: evidence of RNA polymerase III in regulating chromatin configuration

Abstract: We carried out padlock capture, a high-resolution RNA allelotyping method, to study X chromosome inactivation (XCI). We examined the gene reactivation pattern along the inactive X (Xi), after Xist (X-inactive specific transcript), a prototype long non-coding RNA essential for establishing X chromosome inactivation (XCI) in early embryos, is conditionally deleted from Xi in somatic cells (Xi∆Xist). We also monitored the behaviors of X-linked non-coding transcripts before and after XCI. In each mutant cell line,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Additionally, we observed a significant enrichment of SINE elements near promoters of escapees and early reactivated genes in cluster 5 (Supplementary Fig. 4h), a property previously described for escapees and genes prone for reactivation after Xistdepletion 70,71 . Moreover, while we did not detect increased expression levels of early genes in NPCs, where they were still transcriptionally inactive (Supplementary Fig.…”
Section: Esrrb Zfp42supporting
confidence: 74%
“…Additionally, we observed a significant enrichment of SINE elements near promoters of escapees and early reactivated genes in cluster 5 (Supplementary Fig. 4h), a property previously described for escapees and genes prone for reactivation after Xistdepletion 70,71 . Moreover, while we did not detect increased expression levels of early genes in NPCs, where they were still transcriptionally inactive (Supplementary Fig.…”
Section: Esrrb Zfp42supporting
confidence: 74%
“…Padlock capture was performed as previously described 1 , 3 , 15 . Briefly, each reaction was performed in 20 µl volume containing 1 unit Ampligase (A3210K, Epicentre), 1 unit Phusion High-Fidelity DNA Polymerase (M0530, New England BioLabs), 1 x Phusion High-Fidelity DNA Polymerase buffer, 10 nM dNTP and 1 ng padlock probe.…”
Section: Methodsmentioning
confidence: 99%
“…The common linker sequence of each padlock probe allows a common PCR primer pair to amplify all the padlock capture products for deep sequencing. It has been shown that a padlock probe library containing tens of thousands of padlock probes worked efficiently 1 , 3 . Compared with other available methods for targeted sequencing, padlock capture is more suitable for population-based carrier screens, as once synthesized, the padlock library can be easily regenerated by PCR, whereby microarrays or RNA baits used for target enrichment in other methods are expensive and non-reusable 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the XCI status of an X-linked gene can be evaluated by RNA allelotyping of X 129 and X Cast , which provide ample choice of single nucleotide polymorphisms (SNPs). Padlock SNP capture, a high-throughput and high-resolution RNA allelotyping method (19), was performed to profile the XCI status of X linked genes chromosome-wide. The padlock probe library was designed to target 2,969 SNPs covering 1,110 (~55%) of the X-linked genes (19).…”
Section: Atac-seq Was Performed Using Male Es Cell Lines Carrying An mentioning
confidence: 99%
“…Padlock SNP capture, a high-throughput and high-resolution RNA allelotyping method (19), was performed to profile the XCI status of X linked genes chromosome-wide. The padlock probe library was designed to target 2,969 SNPs covering 1,110 (~55%) of the X-linked genes (19). 457 X-linked genes were successfully allelotyped in the experiment.…”
Section: Atac-seq Was Performed Using Male Es Cell Lines Carrying An mentioning
confidence: 99%